Adopsi Inovasi Kehijauan Dalam Mencapai Keunggulan Daya Saing Berkelanjutan - Friska Mastarida (ARBITRASE: Journal of Economics and Accounting, 2022)
The aim of this article is to develop a systematic literature review on the adoption of green innovations in achieving sustainable competitive advantage over the past few decades. The article provides an overview of the theoretical used by previous research. Therefore, this article describes the factors that influence the adoption of green innovation. This study uses a qualitative research design through library research techniques. The author presents various journal publications in the field of marketing and management in several decades using a systematic literature review approach. The research findings found that there are three main pillars to achieve greater excellence, namely environmental health, social health and economic health which are in line with the organization's operational activities. This area of ??research requires a great deal of attention both theoretically and empirically, to analyze and develop new antecedents of green innovation. Further studies emphasize the unique value of other businesses using different perspectives. This article provides a complete framework regarding the importance of sustainable competitive advantage through green innovation